Analisis Penerapan Laporan Keuangan Pada UMKM Berbasis SAK EMKM Pada Toko Eloris Tani Kabupaten Kutai Kartanegara - Gracia Ovelia Ristie; Rr. Marliana (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
"This research was conducted to analyze the application of financial statements based on SAK EMKM in MSMEs Eloris Tani Shop, Marangkayu District, Kutai Kartanegara Regency.This research is a qualitative descriptive research. Data collection techniques were carried out by in-depth interviews, participant observation, and documentation to Eloris Tani Shop. The data analysis technique used is the Miles and Huberman Interactive Analysis Model. Based on the results of the study, it shows that the recording of the financial statements of the Eloris Tani Store is not in accordance with the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) applicable in Indonesia. Eloris Tani Store records its financial statements still simply and manually (Cash Basis), which consists of cash expenses and cash income. Researchers provide recommendations, namely it is hoped that this research can become the basis for Eloris Tani Stores and other MSMEs in starting to record financial statements in accordance with financial accounting standards in Indonesia. Then, for further researchers, it is hoped that they can provide knowledge about the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) to MSMEs that have not recorded financial statements in accordance with financial accounting standards.